ANALYSIS OF THE CHARACTERISTICS OF INTERNATIONAL STANDARD ALGORITHMS «LIGHTWEIGHT CRYPTOGRAPHY» – ISO/IEC 29192-3:2012 - A. S. Poljakov; V. E. Samsonov (Informatika)
The data on the characteristics of international standard algorithms «lightweight cryptography» while application in hardware implementation based on microchips of FPGA are provided. A compari-son of the characteristics of these algorithms with the characteristics of several widely-used standard encryption algorithms is made and possibilities of lightweight cryptography algorithms are evaluated.